Weight loss effect and potentiodynamic polarization response of 1-butyl-3-methylimidazolium chloride ionic liquid in highly acidic medium - Husin, Hazlina; Solo, Bernadine B.; Ibrahim, Izni Mariah; Ong, Hwai Chyuan; Roslan, Azmi (Taylor's University, 2018)
Ionic liquids are increasingly being used as corrosion inhibitors when oil and gas industries started to give focus on sustainability and green impact in their operations. In this study, 1-butyl-3-methylimidazolium chloride ionic liquid in 2M HCl medium has been investigated on mild steel, stainless steel and aluminium bars by using weight loss technique and potentiodynamic polarization measurement. Results showed that 1-butyl-3-methylimidazolium chloride is able to reduce the weight loss of aluminium metal under acidic corrosive surrounding up to 11% compared to that of without the presence of 1-butyl-3-methylimidazolium chloride. Based on potentiodynamic polarization response, percentage of corrosion inhibition efficiency is found to be up to 99.3%. In summary, 1-butyl-3-methylimidazolium chloride is highly potential to act as an anti-corrosion agent, even in a very low concentration.